Elucidation of the Sodium–Copper Extrusion Mechanism in CuCrS2: A High Capacity, Long‐Life Anode Material for Sodium‐Ion Batteries. Issue 5 (24th September 2018) - Krengel, Markus; Hansen, Anna‐Lena; Hartmann, Felix; van Dinter, Jonas; Bensch, Wolfgang
Abstract: The front cover artwork is provided by the group of Prof. Bensch at the inorganic chemistry department of Christian‐Albrechts‐University Kiel (Germany). The image illustrates the copper – sodium extrusion mechanism in CuCrS2 during the first step of sodium uptake. Additionally, the results of ex‐situ X‐ray diffraction measurements and pair distribution function measurements are displayed. Read the full text of the article at10.1002/batt.201800039 . Abstract : " We investigated the copper‐sodium extrusion mechanism of CuCrS2 when applied as an anode in a sodium‐ion battery. Ex‐situ X‐ray diffraction measurements, Rietveld refinements and pair distribution function (PDF) analysis revealed a very complex phase transition in the early stage of Na uptake to form Na 0.70 Cu 0.15 CrS2 followed by full conversion to Cu, Cr and Na2 S. This reaction is highly reversible, leading to a capacity of 424 mAh g −1, even after the 200 th cycle ." Find out more about the story behind the front cover research at10.1002/batt.201800039 .